Tunable Plasmon-Induced Transparency in Dual Hexagonal Resonators With Rotatable Embedded Bar - Yichen Ye; Yiyuan Xie; Tingting Song; Bocheng Liu; Junxiong Chai; Liangyi Zhang; Yunchao Zhu; Yong Liu (IEEE Photonics Journal, 2019)
In this paper, tunable plasmon-induced transparency (PIT) is achieved in a novel and compact plasmonic system which consists of dual hexagonal resonators with rotatable rectangular bar embedded in resonators and a metal-insulator-metal (MIM) waveguide. The proposed structure is numerically investigated by finite-difference time-domain (FDTD) method. The numerical simulation results reveal that by rotating the embedded bar to different angles, PIT can realize in different wavelengths. Tunability in transparency peak wavelength, transmission, and optical delay are also obtained when the angle of embedded bars are changed. In addition, the influences of other structural parameters on transmission and optical delay are analyzed in detail. This proposed structure may provide a novel manipulation for tunable PIT and potentially be applied in highly integrated optical storage and switch devices.